Imagining Evil - Morton, Adam (Les ateliers de l'éthique / The Ethics Forum, 2010)
It is in a way easier to imagine evil actions than we often suppose, but what it is thus relatively easy to do is not what we want to understand about evil. To argue for this conclusion I distinguish between imagining why someone did something and imagining how they could have done it, and I try to grasp partial understanding, in part by distinguishing different imaginative perspectives we can have on an act. When we do this we see an often unnoticed asymmetry: we do not put the same demands on our understanding of wrongdoing as on that of most everyday, morally acceptable, actions.